RANCANG BANGUN PROTOTIPE SISTEM BATTERY CHARGER DENGAN METODE PENGISIAN TIGA TAHAP DI PERUMDA AIR MINUM TIRTA SANJIWANI UNIT PRODUKSI BLANGSINGA - Mangun Yasa, Made Galang; Indra Partha, Cokorde Gede; Arta Wijaya, I Wayan (Jurnal SPEKTRUM; Vol 11 No 1 (2024): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2024.v11.i01.p20, 2024)
Generator set (genset) is needed in companies that operate continuously such as at Perumda Air Minum Tirta Sanjiwani to supply electrical equipment when there is a disruption in the main supply, therefore, the generator set must always be ready to use, one way is through charging the battery with the right method to maintain battery capacity to always be in full condition. This research discusses related to the Battery Charger System Prototype which integrates microcontroller components, sensors, actuators, indicators, and converters to be able to charge the battery with a three-stage charging method and be able to perform a preventive response when a voltage outside the charging standard is detected to minimize the risk of battery damage. Test results using a 10 Ah capacity battery when the DOD is 50% show that charging through the Bulk Stage lasts for 6 hours 40 minutes with a charging current set at 0.7 A, the Absorption Stage lasts for 1 hour 17 minutes with a charging voltage set at 14.7 V, and the Float Stage is tested for 2 hours with a charging voltage set at 13.65 V. This research also includes two battery charging current options to be implemented to partners, so it is expected to provide adequate solutions.